Anti-Cancer Potential of Sinensetin, a Bioactive Compound against Human Cervical Carcinoma Cells via its Molecular Mechanism of Apoptosis - Abdulaziz S. Alothaim; Abdulaziz S. Alothaim
Cancer is ranked among the world's leading causes of death in 2020 with an estimated 10 million recorded fatalities attributable to the disease. After breast, colorectal, and lung cancer, cervical cancer is the fourth most frequent disease in women worldwide. Each year, there are 6,00,000 new cases and 3,40,000 fatalities due to cervical cancer. HPV (Human Papilloma Virus), the main cause of cervical cancer, spreads to the cervix's epithelial cells during intercourse. Aim: The use of natural products in conjunction with chemotherapy treatments is seen to be a viable alternative to chemotherapy medications. Materials and Methods: The purpose of this study was to determine the cytotoxic and apoptotic effects of sinensetin on HepG2 cells. For the determination of cytotoxicity using XXT assay, and LDH release assay, generation of reactive oxygen species was identified by DCFH-DA staining, Nuclear DNA damage was identified by DAPI staining, and apoptotic cell death was detected through AO/EB dual staining, and estimation of pro-apoptotic markers using ELISA method. Results: In the current investigation, the potential of Sinensetin as an anticancer agent for cervical cancer was evaluated. The results showed that apoptosis was induced by Sinensetin in HeLa cells by triggering ROS pathway, DNA damage, and caspase pathway. The cell viability of HeLa cells was reduced with increased concentration of Sinensetin. The LDH level was increased with increased concentration of Sinensetin. Conclusion: All these results suggest that Sinensetin can be used as a potent anticancer drug for cervical cancer.